Readout systems for inner detectors at the LHC and SLHC - Issever, C (2006)
A general overview of the optoelectronic readout and control systems of the ATLAS and CMS inner detectors is given. The talk will also cover challenges and issues of future optoelectronic readout systems at the upgraded LHC (SLHC). First results of radiation tests of VCSELs and optical fibres which were irradiated up to SLHC fluences will be presented. (c) 2006 Elsevier B.V. All rights reserved.